Development and preliminary validation of the spondyloarthritis research consortium of Canada magnetic resonance imaging sacroiliac joint structural score - Walter P. Maksymowych (2018)
Copyright © 2015. All rights reserved. Objective. There is an unmet need for reliable assessment of structural progression in the sacroiliac joints (SIJ) of patients with spondyloarthritis (SpA), but radiography is unreliable and lacks responsiveness. We aimed to develop and validate a new scoring method for structural lesions based on magnetic resonance imaging (MRI), the Spondyloarthritis Research Consortium of Canada (SPARCC) SIJ Structural Score (SSS). The Journal of RheumatologyMethods. The SSS method for assessment of structural lesions is based on T1-weighted spin echo MRI, validated lesion definitions, slice selection according to well-defined anatomical principles, and dichotomous scoring (lesion present/absent) of 5 consecutive slices through the cartilaginous portion of the joint. Scoring ranges are fat metaplasia (0-40), erosion (0-40), backfill (0-20), and ankylosis (0-20). We progressively conducted 3 validation exercises with 2-4 readers on baseline, and either 2-year (exercises 1 and 2) or 1-year (exercise 3) scans from 147 patients with SpA assessed blinded to timepoint. Interobserver reliability was assessed by intraclass correlation coefficient (ICC) and smallest detectable change (SDC).Results. Interobserver reliability for status score was good to excellent for ankylosis (ICC 0.79-0.98), consistently good for fat metaplasia (ICC 0.71-0.78), moderate to good for erosion (ICC 0.58-0.62), and fair to good for backfill (ICC 0.35-0.66). Reliability for change scores was moderate to good for all structural lesions despite the relatively small changes in scores, and was highest for fat metaplasia when both ICC and SDC values were compared.Conclusion. The new SPARCC MRI SSS method can detect structural changes in the SIJ with acceptable reliability over a 1-2-year timeframe, and should be further validated in patients with SpA. (First Release Oct 15 2014; J Rheumatol 2015;42:79-86; doi 10.3899/jrheum.140519).